Breaking the Failed-State Cycle - Haims, Marla C. (RAND Corporation, 2008)
Insecurity in the 21st century appears to come less from the collisions of powerful states than from the debris of imploding ones. This paper aims to improve the understanding and treatment of failed states by focusing on critical challenges at the intersections between security, economics, and politics and on the guiding goal of lifting local populations from the status of victims of failure to agents of recovery.